Analisis Pengaruh Pembelajaran Hibrida Terhadap Motivasi Belajar Siswa SMA pada Masa Pertemuan Tatap Muka Terbatas (PTMT) - Boedi Tjusila; Eric Estha Dahana (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the effect of hybrid learning on the level of preference for face-to-face learning and learning motivation. This research method used a quantitative approach. The research instrument used a questionnaire distributed to 364 high school students in 2022, and the data were analyzed using the Partial Least Square method. Based on the study results, shorter learning duration was related to learning motivation. Students who prefer short learning durations had higher learning motivation. The use of digital technology did not affect learning motivation, and the preference for face-to-face learning was related to learning motivation.